THE INFLUENCE OF THE USE OF THE LEARNING MODEL "PAKUTELA" THROUGH THE MEDIUM OF A SLIDE PRESENTATION AGAINST STUDENT LEARNING MOTIVATION - Helmi, Helmi (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2016)
The research using a quantitative experiment. The research aims to conduct in an effort to enhance learning, motivation, academic achievement and improving the quality of primary school teaching graduates. Research with PAKUTELA models was conducted at the School of Teacher Training and Education (STKIP) Arrahmaniyah Depok. Research with PAKUTELA model study has steps: (a) understand, lecturers give the material to students and the students consider carefully to material explanation of the lecturer; (B) mastered, the lecturer has a fairly heavy responsibility which is to make students able to master all the material provided by the lecturer. The success criteria are at least 80% of the students master the material; (C) Apply, lecturer directing the learning to the application of the lecture material (practical activities); (D) Evaluation, lecturer evaluates the learning activities; (E) Repeat, students are required to repeat the material with the task of granting individuals or groups. PAKUTELA lecturing activities using the models are also aided by the use of presentation media as a supporting medium so that learning becomes more interesting activities. From the analytical research of the data, 80% of the students master the materials. A survey of student opinion data is strongly agreeing 85% of students with the use of PAKUTELA models with presentation media.